Tergitol enables the rapid and inexpensive scoring of nutritional and drug-resistance markers in the progeny of Neurospora crassa genetic crosses - W . Michael Gray; Matthew S. Sachs (Fungal Genetics Reports, 1994)
After cultures from the progeny ascospores of a genetic cross containing nutritional markers are obtained, it is often necessary to test them on a variety of media. Testing using individual culture tubes may be ideal, but is time consuming. In contrast, inoculation of plates with conidial suspensions is relatively quick.